Permanence of a Discrete Periodic Volterra Model with Mutual Interference and Beddington-DeAngelis Functional Response. (9th June 2010) - Wu, Runxin
Abstract : This paper discuss a discrete periodic Volterra model with mutual interference and Beddington-DeAngelis functional response. By using the comparison theorem of difference equation, sufficient conditions are obtained for the permanence of the system. After that, we give an example to show the feasibility of our main result.